Análisis de derecho comparado sobre la protección de bienes patrimoniales de las personas adultas mayores - Salazar Jiménez, María Cristina (2023)
This current curriculum integration project aims to conduct a comparative analysis of elder law concerning the protection of the financial assets of elderly individuals by their relatives or guardians who have legal authority over them, especially when these elderly individuals are of advanced age or suffering from conditions that render them incapable of self- sufficiency or expressing their own will. Safeguarding the financial assets of senior citizens offers benefits to both the State and society, contributing to the full development of the lives of elderly individuals and the effective administration of justice. The majority of senior citizens possess an estate that represents the economic value of their assets and ensures financial stability. However, circumstances such as aging, illness, or social isolation often render elderly individual’s incapable of managing their assets, making them vulnerable to potential exploitation or deception by individuals seeking to appropriate their assets. This can result in mismanagement of assets, wasteful expenditure, or the unproductive utilization of these resources. If these events occur, several adverse effects may directly impact the individuals who are the rightful owners of these assets, such as fraud or deception committed by their family members or strangers, ultimately leading to economic crises, poverty, deprivation, hunger, and abandonment. Therefore, it is established that the State does not guarantee a dignified life for the rightful owners of these rights. Consequently, it is of paramount importance for the State to ensure the protection of the financial assets of elderly individuals until the end of their lives and provide the indispensable legal security necessary for the coexistence of this vulnerable demographic group. This interdisciplinary legal research addresses a socio-legal issue, aiming to identify potential scenarios that may affect the property rights of senior citizens. The research results will be analyzed and assessed to highlight the issues faced by this vulnerable group of individuals and the conflicts that arise when the voluntary actions of elderly individuals in the administration and allocation of their financial assets are hindered. In other words, the limitation of their resources may result in a violation of their rights. Through this research, it has been confirmed that a social issue exists that requires intervention by the State, as the protection of financial assets is not adequately regulated within Ecuadorian legislation. This leaves senior citizens in a state of vulnerability when it comes to safeguarding their assets. It should be noted that the State's mission is to protect the rights of the elderly; unfortunately, this objective has not been fully achieved due to the absence of 5 comprehensive regulations aimed at holistically protecting the most vulnerable members of society.